Mechanism of Earthquake-induced Permanent Deformations in Riverbank Slope and Its Countermeasures - Fathani, Teuku Faisal (2011)
After the occurrence of the Mw 6.3 Mid-Java Earthquake 2006, permanent deformations were found along the riverbank slope of Code River, in the center of Yogyakarta City. About 250 m long and 1-5 cm wide crack causes damage in houses built on a 15-20 m-high steep slope. Further, deformations in the embankment body occurred and the gabion on downslope moved due to seismic induced active lateral earth pressure. This research is aimed at assessing the mechanisms of seismically induced permanent deformations in slopes, and examining appropriate countermeasures. The existing slope stabllity in term of safety factor was calculated by using finite element model considenng phi-c reduction method. The stability ana lysis considers various load conditions, groundwater level and river elevation. The result shows that the safety factor of the existing slope is less than 1.00 with maximum deformation of 111 mm and 211 mm in case of applied fixed load and seismic load, respectively. Furthermore, in order to stop or reduce the deformation, the const ruction of river bank protection in the form of cantilever wall and gabion is designed and examined. It is clarified that several factors affecting slope stability are physical properties of soil materials, external loading condition, slope inclination, groundwater condition, and seismic forces. Other factors that need to be taken into consideration are erosion in the outer river bend and reduction of river wet perimeter that causes erosion on the toe of embankment slope.